PENGARUH PELATIHAN CASE MANAGER TERHADAP KEPUASAAN PASIEN DI RUANG RAWAT INAP INTERNIS RSU SEMBIRING TAHUN 2023 - Damanik, Ayunika Evacauntri; Sarumpaet, Sorimuda; Sari, Nur Mala (Jurnal Kajian Kesehatan Masyarakat, 2024)
based totally on an preliminary survey carried out through researchers, the range of patients inside the IVI Inpatient Room changed into 25 human beings with case managers who had schooling and JASMINE as many as 25 humans with case managers who had not had training. With BPJS status in 2022 (January- September). based totally on information taken from medical facts, certainly one of them is dissatisfaction with the services of nurses and medical doctors and different case managers for the services of inpatients. This research is expected to help optimize the function of case managers as coordinators of nursing services. Hospitals want a layout or approach so that it will carry out a non-stop provider process. One such version of care is the case manager. Case managers who're generally responsible for the coordination and continuity of affected person care while in health facility. The pattern used became Non- chance sampling with saturated sampling technique (census) which was executed in patients in room IVI as the Intervention institution of 25 humans and the JASMINE room as the manage organization of 25 human beings which changed into carried out in December 2023 to February 2023. As for The consequences acquired from this study are that there's an impact of Case supervisor training on affected person pride in the inner Inpatient Room at Sembiring hospital in 2023, each of which has a p- value of 0.001 zero.05 within the Tangibles, Empathy, Reliability, Responsiveness, assurance categories. the results of the Manova check additionally show a significance fee of 0.001 <0.05, so it may be concluded that there is an effect of case manager schooling on affected person delight within the Rau Sembiring Internist Inpatient Room in 2023.